Etika v souvislostech sociální a zdravotní politiky - Liedermanová, Ivana (Univerzita Pardubice, 2013)
Today modern society pays great attention to the development of ethical guidelines for each profession and their implementation in the form of codes of ethics to individual policies. In particular, the Ministry of Health and Welfare is faced in meeting the ethical codes of the current economic and political developments in society. Optimization of standards for health and social care that are implemented through normative no systematic evaluation of the impact on each target group significantly reduces their quality of life. The paper draws attention to the dilemmas of social work and health care in relation to ethics.
Ethics in the context of social and health policy
Keywords: ethics; code of ethics; social care; health care; quality of life; health policy; social policy